Research handbook on remote warfare - Ohlin, Jens David; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
The practice of armed conflict has changed radically in the last decade. With eminent contributors from legal, government and military backgrounds, this Research Handbook addresses the legal implications of remote warfare and its significance for combatants, civilians, policymakers and international lawyers. Primarily focused on the legality of all forms of remote warfare, including targeted killings by drone, cyber-attacks, and autonomous weapons, each chapter gives a compelling insight beyond the standard and reactionary criticisms of these technologies. Current assumptions of remote warfare are challenged and discussed from a variety of international perspectives. These include governing the use of force, humanitarian law, criminal law, and human rights law. Contributors consider the essential features of current warfare regulations, and test their strength for controlling these new technologies. Suggestions are made for the future development of law to control the limits of modern remote warfare, with a particular focus on the possibility of autonomous weapons. This is an essential read for academics and students of jus ad bellum, international humanitarian law, criminal law and human rights. Students of political science, governance and military studies will also find this a thought-provoking insight into modern warfare techniques and the complex legal issues they create.
Introduction -- Part I: the concept of remoteness in warfare -- 1. Remoteness and reciprocal risk / Jens David Ohlin -- 2. The principle of distinction and remote warfare / Emily Crawford -- 3. Modern drone warfare and the geographical scope of application of IHL: pushing the limits of territorial boundaries / Robert Heinsch -- 4. The characterisation of remote warfare under international humanitarian law / Anthony Cullen -- 5. Remoteness and human rights law / Gloria Gaggioli -- 6. Exploiting legal thresholds, fault-lines and gaps in the context of remote warfare / Mark Klamberg -- Part II: remotely piloted vehicles & cyber weapons -- 7. Drone strikes: a remote form of self-defense? / Nigel White & Lydia Davies-Bright -- 8. Drone warfare and the erosion of traditional limits on war powers / Geoffrey Corn -- 9. Developing norms for cyber conflict / William Banks -- 10. Some legal and operational considerations regarding remote warfare: drones and cyber warfare revisited / Terry D. Gill, Jelle van Haaster, & Mark Roorda -- Part III: remoteness through autonomous weapons -- 11. Remote and autonomous warfare systems: precautions in attack and individual accountability / Ian Henderson, Patrick Keane, Josh Liddy -- 12. Autonomous weapons systems: a paradigm shift for the law of armed conflict / Robin Geiß and Henning Lahmann -- 13. Making autonomous targeting accountable: command responsibility for computer-guided lethal force in armed conflicts / Peter Margulies -- 14. The strategic implications of lethal autonomous weapons / Michael Meier -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: drony; bezpilotní letadla; kybernetická válka; informační válka; drones; unmanned aircraft; cyberwarfare; information warfare; e-knihy online; e-books online